Interferon-alpha treatment for chronic hepatitis C in children - Yüce, Aysel; Koçak, Nurten; Gürakan, Figen; Özen, Hasan (The Turkish Journal of Pediatrics, 2000)
Interferon-alpha therapy has been proven efficient in chronic hepatitis C infection. Although it has been used as a standard therapy in adults, there are limited data on benefits of interferon treatment in children. We conducted a study of recombinant interferon-alpha therapy in 10 children with chronic hepatitis C. They had high aminotransferase values and positive antibodies to hepatitis C virus and HCV-RNA for at least six months. Interferon-alpha was given at a dosage of 5 million units/m² body surface three times a week for six months. At the end of therapy, five (50%) of the patients had complete response and two partial response. Three patients were nonresponders. Eight of the patients could be followed up for six months after stopping therapy, at which point one of the four complete responders and a partial responder relapsed. One of the three nonresponders had complete response at 12 months. Eventually, four (50%) of eight patients were complete responders. All of the nonresponders were the patients with previous malignant diseases. These findings suggest that interferon-alpha has beneficial effects in children with chronic hepatitis C, and a six month therapy seems to be reasonable. Patients with underlying malignant disease are not good candidates for interferon treatment.